Pre‐Oxidation‐Tuned Microstructures of Carbon Anodes Derived from Pitch for Enhancing Na Storage Performance. Issue 27 (9th August 2018) - Lu, Yaxiang; Zhao, Chenglong; Qi, Xingguo; Qi, Yuruo; Li, Hong; Huang, Xuejie; Chen, Liquan; Hu, Yong‐Sheng
Abstract: Disordered carbons have captured extensive interest as anode materials for Na‐ion batteries (NIBs) due to the abundant resources, competitive specific capacity, and low cost. Here, a facile strategy of pre‐oxidation is successfully adopted to tune the microstructure of carbon anode to facilitate sodium storage. Pitch is selected as the low‐cost and high carbon yield precursor. An easy pre‐oxidation treatment in air can enable pitch to realize an effective structural conversion from ordered to disordered at further carbonization processes. Compared with the carbonized pristine pitch, the carbonized pre‐oxidation pitch increases the carbon yield from 54 to 67%, the sodium storage capacity from 94.0 to 300.6 mAh g −1, and the initial Coulombic efficiency from 64.2 to 88.6%. Experiment results reveal that the introduction of oxygen based functional groups is the key to achieve the highly disordered structure, not only ensuring the cross‐linkage during low‐temperature pre‐oxidation process but also suppressing the carbon structure from melting and rearranging in the high‐temperature carbonization process. Most importantly, this facile pre‐oxidation strategy can also be extended to other carbon precursors to facilitate the low‐cost and high‐performance disordered carbon anodes for NIBs and beyond. Abstract : A disordered carbon anode for Na‐ion batteries with both low cost and high performance is achieved via a simple pre‐oxidation of pitch in air followed by high‐temperature carbonization, during which the electrochemical behavior is modulated from possessing only a sloping region to featuring both sloping and plateau regions and a threefold capacity improvement is attained through this microstructure tuning.